2016
DOI: 10.1111/dar.12438
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion criteria in treatment research on alcohol, tobacco and illicit drug use disorders: A review and critical analysis

Abstract: Although some eligibility criteria are necessary to protect participant safety and ensure internal validity, researchers conducting studies on substance use disorder treatments should thoughtfully consider the justification for and specific operationalisation of the extensive exclusion criteria they often utilise. [Moberg C, Humphreys K. Exclusion criteria in treatment research on alcohol, tobacco and illicit drug use disorders: A review and critical analysis. Drug Alcohol Rev 2017;36:378-388].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Prospective investigational studies conducted in a research context according to study protocols reported much higher adherence rates over time compared to retrospective medical record review studies taken from routine clinical care settings. The reasons for this large divergence are unclear but may include differences between samples owing to study exclusion criteria (71, 72) and a host of procedural differences between investigational studies and routine clinical care (e.g., study compensation, medication cost, follow-up efforts, expertise and familiarity with XR-NTX, contact with healthcare staff) (73). The observed difference in adherence between these two types of studies should be interpreted cautiously, however.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective investigational studies conducted in a research context according to study protocols reported much higher adherence rates over time compared to retrospective medical record review studies taken from routine clinical care settings. The reasons for this large divergence are unclear but may include differences between samples owing to study exclusion criteria (71, 72) and a host of procedural differences between investigational studies and routine clinical care (e.g., study compensation, medication cost, follow-up efforts, expertise and familiarity with XR-NTX, contact with healthcare staff) (73). The observed difference in adherence between these two types of studies should be interpreted cautiously, however.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Humphreys et al (12) found that 20% to 33% of patients with alcohol use disorders would be excluded by the eligibility criteria commonly used in RCTs of alcohol use disorders, whereas, Okuda et al (2) found that as many as 80% of patients with cannabis dependence would be excluded by the commonly used eligibility criteria for cannabis treatment RCTs. A recent review study by Moberg and Humphreys (13) estimated that commonly used exclusion criteria in SUD trials would exclude between 64% and 95% of potential participants.…”
Section: Introductionmentioning
confidence: 99%
“…New definitions (ASMM, 2011) have replaced those created in the last century, centered on twelve step understanding, which emphasizes powerlessness [6]. Today's cutting edge perspective utilizes concepts of powerfulness in taking responsibility for recovery, initiating life style change, creating health and wellbeing [7,8].…”
Section: Introductionmentioning
confidence: 99%